2009
DOI: 10.3113/fai.2009.0512
|View full text |Cite
|
Sign up to set email alerts
|

ChevronOsteotomy with Lateral Release and Adductor Tenotomy For Hallux Valgus

Abstract: Our short-term results show that distal chevron osteotomy combined with lateral release and adductor tenotomy is a feasible surgical option to address mild to moderate hallux valgus deformity, even with an IM angle between 15 and 20 degrees. Clinical and radiographic outcomes are generally good and patient satisfaction is generally high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15] This includes our previous report demonstrating that the combined method provides an effective and reliable means of correcting moderate to severe hallux valgus deformity with high levels of patient satisfaction and a low incidence of complications. 15 Potenza et al 16 reported that distal chevron osteotomy with lateral release and adductor tenotomy could be used in patients with an increased IMA with satisfactory results. Our results of distal chevron osteotomy are similar to previous studies of proximally placed osteotomy for severe hallux valgus deformity as shown in Table V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15] This includes our previous report demonstrating that the combined method provides an effective and reliable means of correcting moderate to severe hallux valgus deformity with high levels of patient satisfaction and a low incidence of complications. 15 Potenza et al 16 reported that distal chevron osteotomy with lateral release and adductor tenotomy could be used in patients with an increased IMA with satisfactory results. Our results of distal chevron osteotomy are similar to previous studies of proximally placed osteotomy for severe hallux valgus deformity as shown in Table V.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Several recent studies have demonstrated that distal chevron osteotomy in conjunction with a distal soft-tissue procedure could enhance the amount of correction, suggesting that this combination can be applied to more severe deformities with a successful outcome. [9][10][11][12][13][14][15][16] However, a risk associated with a distal chevron osteotomy is avascular necrosis of the metatarsal head, 5,17 and an osteotomy combined with a distal softtissue procedure might increase the incidence of avascular necrosis. 11,15 The purpose of the present study was to compare the clinical and radiological outcomes between proximal chevron and distal chevron osteotomy combined with a soft-tissue procedure in severe hallux valgus deformity.…”
mentioning
confidence: 99%
“…From the literature review, proximal metatarsal osteotomy has been chosen as a major operation for moderate to severe HV, due to its superior power of correction; however, potential barriers are complicated surgical technique, longer incision, longer operating time and higher sequential complications when compared with DMO [4,25,27]. On the other hand, DMO has been popularized in some regions of the world because it is easier, requires a shorter incision, has fewer complications and improves pain and functional ability in a wider range of deformities [4,28,29]. In general, DMO is recommended for mild to moderate HV [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…This soft tissue procedure aims to restore the physiological balance of capsular, ligamentous and muscular structures around the first metatarsophalangeal (MTP) joint. During the last decades worldwide scientific discussions, clinical surveys [1][2][3][4][5][6][7][8], anatomical studies [9,10] and experimental set-ups [11][12][13][14] have helped to clarify open questions about soft tissue procedures: is it necessary in every case of bunion surgery and is there a technique superior in respect of high efficiency and low risk? Certain reservations exist regarding the combination of distal soft tissue procedures and distal metatarsal osteotomies.…”
Section: Introductionmentioning
confidence: 99%